The interplay between oxidative stress and autophagy in chronic obstructive pulmonary disease - Zhao, Xiaoyu; Zhang, Qiang; Zheng, Rui (Frontiers in Physiology, 2022)
Autophagy is a highly conserved process that is indispensable for cell survival, embryonic development, and tissue homeostasis. Activation of autophagy defends cells against oxidative stress and is a major adaptive response to injury. When autophagy is dysregulated by factors such as smoking, environmental damage and aging, it can lead to enhanced formation of aggressors and production of reactive oxygen species (ROS), resulting in oxidative stress and oxidative damage to cells. ROS activates autophagy, which in turn promotes cell adaptation and reduces oxidative damage by degrading and circulating damaged macromolecules and dysfunctional cell organelles. The cellular response triggered by oxidative stress includes changes in signaling pathways that ultimately regulate autophagy. Chronic obstructive pulmonary disease (COPD) is the most common lung disease among the elderly worldwide, with a high mortality rate. As an induced response to oxidative stress, autophagy plays an important role in the pathogenesis of COPD. This review discusses the regulation of oxidative stress and autophagy in COPD, and aims to provide new avenues for future research on target-specific treatments for COPD.